2017
DOI: 10.1016/j.coastaleng.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of nonlinear wave-induced seabed response around mono-pile foundation

Abstract: Stability and safety of offshore wind turbines with mono-pile foundations, affected by 17 nonlinear wave effect and dynamic seabed response, are the primary concerns in offshore 18 foundation design. In order to address these problems, the nonlinear wave effect on dynamic 19 seabed response in the vicinity of mono-pile foundation is investigated using an integrated model, 20 developed using OpenFOAM, which incorporates both wave model (waves2Foam)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 50 publications
2
48
1
Order By: Relevance
“…An alternative hybrid foundation system comprising a monopile and a bearing plate (or skirted footing) has been demonstrated to enhance the lateral bearing capacity compared with a monopile [96][97][98][99]. Nevertheless, the enhanced capacity of the hybrid foundation largely relies on the proper interaction between the bearing plate and the soils at the shallow zone of the seabed, where local scour and wave-induced pore pressure could occur [100][101][102][103][104][105][106][107][108]. The extent of local scour and scour effects on both the bearing capacity and natural frequency of a hybrid monopile need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative hybrid foundation system comprising a monopile and a bearing plate (or skirted footing) has been demonstrated to enhance the lateral bearing capacity compared with a monopile [96][97][98][99]. Nevertheless, the enhanced capacity of the hybrid foundation largely relies on the proper interaction between the bearing plate and the soils at the shallow zone of the seabed, where local scour and wave-induced pore pressure could occur [100][101][102][103][104][105][106][107][108]. The extent of local scour and scour effects on both the bearing capacity and natural frequency of a hybrid monopile need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The wave sub-model is based on the FDM solved equation in Flow 3D framework, while the COMSOL Multiphysics [28] software was used to establish the seabed sub-model, which the FEM solved-equation is assigned as the governing equation. Numerous studies in the past have employed these set of equations in the investigation of the WSSI around offshore pipelines [29,30] breakwater structures [31,32] and offshore pile structures [20,21].…”
Section: Theoretical Modelmentioning
confidence: 99%
“…However, not much consideration has been given to the oscillatory wave-induced seabed response around these structures. In most recent time, the numerous investigation on 3-dimensional numerical studies on wave-induced response around pile structures has focused most of their attention around the monopile structure [15][16][17][18][19][20][21]. However, some few studies have carried out on gravity-based support structure [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field observations of some project cases have shown that wave loads do not usually cause direct damage to the strength or stiffness of an offshore structure but they often lead to the seabed liquefaction of the region that surrounds the offshore structure and subsequently result in the partial or total loss of bearing capacity [5][6][7][8]. Pile foundations, pipelines and breakwaters have received great attention in the study of wave-seabed-structure interactions [9][10][11], whereas cofferdams have been neglected in such investigations. Therefore, the study of the wave-induced seabed response around cofferdams is of great significance to the safety control during civil engineering construction.…”
Section: Introductionmentioning
confidence: 99%